Nitrate-assisted photocatalytic efficiency of defective Eu-doped Pr(OH)3 nanostructures. Issue 47 (23rd November 2017) - Aškrabić, S.; Araújo, V. D.; Passacantando, M.; Bernardi, M. I. B.; Tomić, N.; Dojčinović, B.; Manojlović, D.; Čalija, B.; Miletić, M.; Dohčević-Mitrović, Z. D.
Abstract : Eu-doping of Pr(OH)3 1D nanostructures induces photocatalytic properties in the otherwise adsorptive material. Oxygen vacancies, the change in the morphology and the presence of Eu 3+ and NO3 − ions play a significant role in the effect. Abstract : Pr(OH)3 one-dimensional nanostructures are a less studied member of lanthanide hydroxide nanostructures, which recently demonstrated an excellent adsorption capacity for organic pollutant removal from wastewater. In this study, Pr1− x Eu x (OH)3 ( x = 0, 0.01, 0.03, and 0.05) defective nanostructures were synthesized by a facile and scalable microwave-assisted hydrothermal method using KOH as an alkaline metal precursor. The phase and surface composition, morphology, vibrational, electronic and optical properties of the as-prepared samples were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), inductively coupled plasma optical emission spectrometry (ICP-OES), transmission electron microscopy (TEM), field emission scanning electron microscopy (FE-SEM), Raman, infrared (IR), photoluminescence (PL), and diffuse reflectance spectroscopy (DRS). It was deduced that the incorporation of Eu 3+ ions promoted the formation of oxygen vacancies in the already defective Pr(OH)3, subsequently changing the Pr(OH)3 nanorod morphology. The presence of KNO3 phase was registered in the Eu-doped samples. The oxygen-deficient Eu-doped Pr(OH)3 nanostructures displayed an improved photocatalytic activity in the removal of reactive orange (RO16) dye under UV-vis light irradiation. An enhanced photocatalytic activity of the Eu-doped Pr(OH)3 nanostructures was caused by the synergetic effect of oxygen vacancies and Eu 3+ (NO3 − ) ions present on the Pr(OH)3 surface, the charge separation efficiency and the formation of the reactive radicals. In addition, the 3% Eu-doped sample exhibited very good adsorptive properties due to different morphology and higher electrostatic attraction with the anionic dye. Pr1− x Eu x (OH)3 nanostructures with the possibility of tuning their adsorption/photocatalytic properties present a great potential for wastewater treatment.